Atrial fibrillation inducibility after pulmonary vein isolation under general anaesthesia - Skala, Tomas; Tudos, Zbynek; Moravec, Ondrej; Hutyra, Martin; Precek, Jan; Skalova, Jitka; Klementova, Olga; Zapletalova, Jana; Taborsky, Milos (Biomedical papers, 2020)
Aims: Atrial fibrillation (AF) inducibility with rapid atrial pacing following AF ablation is associated with higher risk of AF recurrence. The predictive value of AF inducibility in paroxysmal AF patients after pulmonary vein isolation (PVI), done under general anaesthesia (GA), remains questionable since GA might alter AF inducibility and/or sustainability. Methods: Consecutive patients (n = 120) with paroxysmal AF without prior catheter ablation (CA) were enlisted in the study. All patients were ablated under GA. We have used a point-by-point CA and elimination of dormant conduction after adenosine in all patients. A predefined stimulation protocol was used to induce arrhythmias after PVI. Regular supraventricular tachycardias were mapped and ablated. Patients were divided into 3 subgroups - noninducible, inducible AF with spontaneous termination in five minutes, inducible AF without spontaneous termination. During 12 months of follow-up, all patients were examined four-times with 7-day ECG recordings. Results: There was no statistical difference between the three subgroups in a rate of arrhythmia recurrence (11.1 vs. 27.5 vs. 27.3%, P=0.387), despite a clear trend to a better success rate in the non-inducible group. The subgroups did not differ in left atrial (LA) diameter (41.0 extpm6, 43.0 extpm7, 42.0 extpm5 mm, P=0.962) or in any other baseline parameter. Conclusion: AF inducibility as well as presence or absence of its early spontaneous termination after PVI done under general anaesthesia in paroxysmal AF patients were not useful as predictors of procedural failure.
Keywords: atrial fibrillation; pulmonary veins isolation; inducibility; general anaesthesia